Interesting Linguistic Features in Coreference Annotation of an Inflectional Language - Ogrodniczuk, Maciej; Głowińska, Katarzyna; Kopeć, Mateusz; Savary, Agata; Zawisławska, Magdalena (Chinese Computational Linguistics and Natural Language Processing Based on Naturally Annotated Big Data, 2013)
This paper reports on linguistic features and decisions that we find vital in the process of annotation and resolution of coreference for highly inflectional languages. The presented results have been collected during preparation of a corpus of general direct nominal coreference of Polish. Starting from the notion of a mention, its borders and potential vs. actual referentiality, we discuss the problem of complete and near-identity, zero subjects and dominant expressions. We also present interesting linguistic cases influencing the coreference resolution such as the difference between semantic and syntactic heads or the phenomenon of coreference chains made of indefinite pronouns.